Designing the Internet of things - McEwen, Adrian; Cassimally, Hakim (Chichester : Wiley, 2013)
Explores the platforms available for developing hardware or software, offers unique design concepts, and shows the ways to scale up from a single prototype to mass production.
Includes index.
Keywords: Electronic apparatus and appliances -- Design and construction; Ubiquitous computing